(untitled) (Italian Journal of Public Health, 2012)
Background: The relationship between single and/or multiple social roles that women hold (occupa- tional, partner, and parent) and health and sickness absence is an important public health issue. Few studies on the social roles held by women have been performed in the Swedish context of gender equality. The aim of this study was to analyse associations between occupational, partner and parent roles (and combinations of these roles) and their relation to self-rated physical health, psychiatric disorders and long-term sickness absence in a population based sample of women in Sweden. MeThodS: Women born in 1935, 1945, 1955, 1965, 1970 or 1975 (n=600) were interviewed at baseline and five years later. cross-sectional data were analysed with multivariate logistic regression analysis adjusted for age, socio-economic position, alcohol dependence and abuse. reSulTS: an occupational role was associated with lower odds for poor self-rated physical health, 0.28 (0.10-0.82), and sickness absence, 0.25 (0.10-0.86). a partner role was associated with lower odds for psy- chiatric disorder, 0.58 (0.35-0.98) while a parental role (children < 14 years) was associated with higher odds for sickness absence, 4.17 (1.86-9.38). The combination of holding an occupational and partner role was associated with lower odds for health outcomes compared with having three roles. conclusion: holding an occupational and partner role was related to lower odds for poor self-rated physical health, psychiatric disorder and long-term sickness absence, while having a parental role was adversely related to sickness absence. results are important in the light of discussions on reconciliation of work and family, and are of interest in countries with high or increasing female labour force participation.